Imaging Evaluation of Mesenteric Ischemia: Is There a Golden Period for This Entity? - Ishfaq Zargar; Irfan Robanni; Omair Shah; Tariq Gojwari; Riaz Rasool; Naseer Choh; Faiz Shera; Munir Wani (Galician Medical Journal, 2022)
Background.The study was aimed at assessing the role of ultrasonography and multidetector computed tomography angiography in evaluating patients with suspected mesenteric ischemia, as well as assessing the effect of the time from presentation to management on mortality and morbidity.